Handling Covid-19 Related to Regional Security According to ASEAN Political-Security Community - Calvin, Calvin (Universitas Negeri Semarang, 2020)
The presence of COVID-19, caused enourmous losses to the society and nation in various aspects of life. One aspect which meant is state security especially in ASEAN.Speaking of the present, no antidote has been completely found to cure COVID-19. This paper is made to find out what effort has been done by South East Asia countries in the aspect of state security, and to find out what effort has been done by ASEAN Political-SecurityCommunity. The author uses juridical-normative research method, which the author did the research based on national and international instruments of law, doctrines, literature andother media.Based on the research results, ASEAN members haveissuedvarious policies in purpose to deal with COVID-19 such as: travel ban, social distancing/ physical distancing, and lockdown. Furthermore, all efforts made by ASEAN Political-Security Communityare categorized as soft law.